Dioscin attenuates renal ischemia/reperfusion injury by inhibiting the TLR4/MyD88 signaling pathway via up-regulation of HSP70. (October 2015) - Qi, Meng; Zheng, Lingli; Qi, Yan; Han, Xu; Xu, Youwei; Xu, Lina; Yin, Lianhong; Wang, Changyuan; Zhao, Yanyan; Sun, Huijun; Liu, Kexin; Peng, Jinyong
Graphical abstract: Abstract: We previously reported the effect of dioscin against hepatic ischemia/reperfusion injury (IRI) in rats. However, little is known concerning the role of dioscin in renal IRI. In the present study, rats were subjected to IRI and dioscin was intragastrically administered for seven consecutive days before surgery. In vitro models of hypoxia/reoxygenation were developed in NRK-52E and HK-2 cells, which were prophylacti -cally treated with or without dioscin. The results showed that dioscin significantly decreased serum BUN and Cr levels, and markedly attenuated cell injury. Mechanistic studies showed that dioscin significantly increased HSP70 levels, decreased the levels of TLR4, MyD88, TRAF6, COX-2, JNK, ERK and p38 MAPK phosphorylation, suppressed the nuclear translocation of NF-κB and HMGB1, and subsequently decreased the mRNA levels of IL-1β, IL-6, TNF-α, ICAM-1 and IFN-γ. Moreover, HSP70 siRNA or TLR4 DNA reversed the nephroprotective effects of dioscin, while dioscin still significantly down-regulated the TLR4 signaling pathway. Furthermore, by inhibiting MyD88 with ST2825 (a MyD88 inhibitor), renal IRI was significantly attenuated, suggesting that the effect of dioscin against renal IRI depended on MyD88. Our results suggested that dioscin had a potent effect against renal IRI through suppressing the TLR4/MyD88 signaling pathway by up-regulating HSP70. These data provide new insights for investigating the natural product with the nephroprotective effect against IRI, which should be developed as a new therapeutic agent for the treatment of acute kidney injury in the future.